The Influence of Work Flexibility and Job Stress on Employee Turnover Intention - Ramdani, Fikri (Talent: Journal of Economics and Business, 2023)
Turnover intention refers to an employee's tendency or intention to leave their job or organization. This is an initial indication of the possibility of employee transfer from one position or company to another position or company. Turnover turnover rates can provide important insights for human resource management and organizational leaders about employee satisfaction, their perceptions of the work environment, and other such factors that may influence their decisions to stay or leave. This research aims to find out how much influence work flexibility and work stress have on employee turnover intention. The method used in this research is a quantitative method which is carried out by distributing questionnaires containing statements regarding the influence of work flexibility and work stress on employee turnover intention. This research took samples from workers in several areas and produced quite a lot of respondents. The results of the questionnaire data show that work flexibility has no effect on work stress and work flexibility has no effect on turnover intention, while work stress has a positive effect on turnover intention, which means it has an effect.